2017
DOI: 10.1139/facets-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 24-h naproxen dose on hydration and electrolyte measures during moderate-intensity cycling in the heat

Abstract: Few controlled laboratory studies have examined the negative effects non-steroidal anti-inflammatory drugs can have on fluid-electrolyte balance during exercise. Our objective was to determine whether a 24-h naproxen dose negatively affected hydration and electrolyte measures before, during, and 3 h after 90 min of cycling in a hot or ambient environment. Using a double blind, randomized and counterbalanced cross-over design, 11 volunteers (six male, five female) completed four trials, with conditions as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…16 The current study showed that the elderlies' consumption of antiinflammatory drugs can be ranked second only to their consumption of anti-acids. With regard to this aspect, the observations of the present study agree with those of Emerson et al, 17 who, in their study conducted in the United States principally dealing with the use of non-steroidal anti-inflammatory drugs (NSAIDs), emphasized the dangers of taking anti-inflammatories in the elderly. Prostaglandins, which are hormones that regulate blood flow to the kidneys, are inhibited by NSAIDs.…”
Section: Discussionsupporting
confidence: 92%
“…16 The current study showed that the elderlies' consumption of antiinflammatory drugs can be ranked second only to their consumption of anti-acids. With regard to this aspect, the observations of the present study agree with those of Emerson et al, 17 who, in their study conducted in the United States principally dealing with the use of non-steroidal anti-inflammatory drugs (NSAIDs), emphasized the dangers of taking anti-inflammatories in the elderly. Prostaglandins, which are hormones that regulate blood flow to the kidneys, are inhibited by NSAIDs.…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned, this study was part of a larger project; we previously reported no significant differences between experimental conditions for hydration, maximum HR, perceived GI symptoms (e.g., cramping, bloating, nausea), or performance measures. 31 , 41 Dietary analysis revealed no significant differences in calories, protein, fats, and carbohydrates 1-day prior to data collection. No differences were found in macronutrient intake the morning of the trials (i.e., small meal prior to arriving) between conditions.…”
Section: Resultsmentioning
confidence: 96%
“…Upon arrival at the laboratory for data collection, we verbally asked participants if they took the 2 pills and then provided them their third pill. We obtained a urine sample to verify participants were euhydrated, 41 and obtained a baseline Tc and blood sample. Participants completed the 90-min cycling bout and researchers continuously monitored Tc and HR.…”
Section: Methodsmentioning
confidence: 99%
“…To control for other factors that may influence GI symptoms, Spearman's rho correlations were run for maximum HR, maximum RPE, and distance. Specific Tc results are not presented as part of this study and hydration results are published elsewhere 30 ; spearman's rho correlations were conducted for GI symptoms to Tc at the end of the 10 min maximum effort and fluid volume during exercise to determine potential effects.…”
Section: Methodsmentioning
confidence: 99%